Cadmium Treatment Alters the Expression of Five Genes at the Cda1 Locus in Two Soybean Cultivars [Glycine Max (L.) Merr] - Yi Wang; Xue Xiao; Tiequan Zhang; Houyang Kang; Jian Zeng; Xing Fan; Lina Sha; Haiqin Zhang; Kangfu Yu; Yonghong Zhou (The Scientific World Journal)
Westag 97 has larger capacity of Cd accumulation in roots which prevents Cd from translocating into stems and leaves; conversely, AC Hime has smaller capacity of Cd accumulation in roots; more Cd is transported into stems and leaves. The different capacity of Cd in roots between Westag 97 and AC Hime causes the different Cd concentration in seeds. Meanwhile, according to the different expression levels of RSTK, ISCP, and H+-ATPase between Westag 97 and AC Hime, RSTK may be involved in transporting Cd into stems and leaves; H+-ATPase may be correlated to the capacity of Cd accumulation in roots; and Cd caused some changes of fundamental life process which leaded to the different expression patterns of ISCP between Westag 97 and AC Hime.